Different Aspects of the Neural Response to Socio-Emotional Events Are Related to Instability and Inertia of Emotional Experience in Daily Life: An fMRI-ESM Study - Provenzano, Julian; Bastiaansen, Jojanneke A.; Verduyn, Philippe; Oldehinkel, Albertine J.; Fossati, Philippe; Kuppens, Peter (Frontiers in Human Neuroscience, 2018)
Emotions are fundamentally temporal processes that dynamically change over time. This temporal nature is inherently involved in making emotions adaptive by guiding interactions with our environment. Both the size of emotional changes across time (i.e. emotional instability) and the tendency of emotions to persist across time (i.e. autocorrelation of emotional experience, emotional inertia) are key features of a person’s emotion dynamics, and have been found central to maladaptive functioning and psychopathology as well as linked to social functioning. However whether different (neural) mechanisms are underlying these dynamics as well as how they are related to the processing of (socio-)emotional information is to date widely unknown. Using a combination of Experience Sampling methods and fMRI (involving a social feedback paradigm), we examine how emotional instability and inertia in everyday life are associated with different aspects of the neural response to socio-emotional events. The findings indicate that while emotional instability is connected to the response of the core salience network, emotional inertia is associated to responses in the parahippocampal gyrus and lateral orbitofrontal cortex. This is the first study showing that different aspects of the neural response to socio-emotional events are associated with different aspects of the temporal dynamics of emotion in real life.